Changes in Escherichia coli Associated with Acquired Tolerance for Quaternary Ammonium Compounds - Maxcy, R. B. (1971)
Acquired tolerance for a quaternary ammonium compound produced a tolerance for a similar compound. Tolerance was associated with the structure and the extent of adsorption of the compound. Morphological changes and resistance to disruption by pressure and by sonic treatment accompanied the development of tolerance. An otherwise weakened culture evolved with the acquisition of tolerance. The maximum obtainable viable population density of tolerant cells in growth medium was approximately 5% of that obtained in the parent culture. Tolerant cultures died off more rapidly in the original growth medium as well as when washed cell suspensions were stored at 5 C. Since acquired tolerance was associated with an otherwise weakened culture, the occurrence of the tolerant cells to limit the efficacy of quaternary ammonium compounds in sanitation operations is highly unlikely.